Electron-phonon scattering effects on electronic and optical properties of orthorhombic GeS - Villegas, Cesar E. P. [UNESP]; Rocha, A. R. [UNESP]; Marini, Andrea (American Physical Society (APS), 2016)
Group-VI monochalcogenides are attracting a great deal of attention due to their peculiar anisotropic properties. Very recently, it has been suggested that GeS could act as a promissory absorbing material with high input-output ratios, which are relevant features for designing prospective optoelectronic devices. In this work, we use the ab initio many-body perturbation theory to study the role of electron-phonon coupling on orthorhombic GeS. We identify the vibrational modes that efficiently couple with the electronic states responsible for giving rise to the first and second excitonic state. We also study finite-temperature optical absorption, and we show that even at T→0K, the role of the electron-phonon interaction is crucial to properly describe the position and width of the main experimental excitation peaks. Our results suggest that the electron-phonon coupling is essential to properly describe the optical properties of the monochalcogenides family.